MUSIC IN THE CARIBBEAN ISLANDS: ROLE OF REGGAE MUSIC AND TOURISTIC CULTURE IN JAMAICA - CHANG LEE (ASEAN Journal on Hospitality and Tourism, 2008)
Reggae music is more than a popular music style. It has been an essential part of tourism development in Jamaica. The way in which reggae music has been interpreted since its inception is critical to understanding the music 's effect on Jamaica's touristic culture. This touristic culture describes the established social atmosphere of the community and attitude of local residents and visitors toward tourism within the region. The Jamaican government's effort to control the social movement and the role of reggae music in relation to tourism are viewed by understanding reggae music with respect to the Rastafarian movement. Governmental approaches played an important part in allowing the development of touristic culture with reggae music and the Rastafarian movement. The purpose of this study was to view the role of reggae music in Jamaican tourism development along with a social movement, the Rastafarian movement. This study was important because it served as a vehicle to understand the interplay of social movement and touristic culture. Such an understanding of touristic culture could be useful in tourism dependent regions. This study used an extensive review and analysis of the literature to make observations and conclusions.